Analisis Kepuasaan Pengguna Aplikasi GRAB Sebagai Transportasi Online Dengan Metode TAM - Elan, Melania Seindang; Muslikh, Ahmad Rofiqul (LPPM STIKI MALANG, 2024)
Grab is a company that provides digital-based transportation services that continues to improve the quality of its services. Grab offers a variety of service options, from transportation, goods delivery, to food delivery. Problems with the Grab application, such as usage problems, inaccurate location points, and fictitious orders, have an impact on consumer satisfaction. Analysis of aspects that impact satisfaction is needed to assess application performance and consumer satisfaction levels. The goal of this observation is to measure user satisfaction which can ultimately provide an overview of the success of implementing the system based on user perceptions using the TAM method. This research method uses TAM. The use of TAM in this research uses 5 variables in TAM including Perceived Ease of Use, Perceived Usefulness, Behavioral Intention, Actual Use, and Attitude Toward Using. The results obtained from this research in the form of independent variables have a contribution of 74.8% to user satisfaction, while the remaining 25.2% has an impact from other variables that are not present in this form of linear regression. This means that the independent variable has a contribution of 74.8% to user satisfaction, while the remaining 25.2% has an impact from other variables that are not present in this form of linear regression.